Reception and performance in high level male volleyball: A relational study - López, E.; Díez-Vega, I.; Molina, J. J. (Journal of Human Sport & Exercise, 2022)
The aim of this study was to know the association of the reception zone on the performance of the reception of the high-performance male volleyball teams, considering the impact of rotation. The sample consist of 4223 KI sequences, belonging to 29 men's matches of world national teams of the highest level played between 2012 and 2016. The 3 main variables were: the rotation of the team in reception; the reception area; and the reception performance. For data analysis, Pearson's Chi-square analysis has been used to determine the influence of rotation in the reception area, and ordinal regression models to determine the influence of the reception area and the interaction of rotation on the reception performance. The level of significance was set at p = .05. Results showed differences in the distribution of the serve depending on the team's rotation (p < .001; V = 0.123). Significant relationships and interactions were also found between the rotation of the equipment and the reception area, that allow us to understand the greater or lesser probability of achieving a better reception performance (p < .001). In conclusion, the reception area is associated with the rotation of the team, which seems to be related to tactical decisions during the serve of the rival team. Furthermore, the reception performance is different depending on the rotation of the equipment, the reception area, and the interaction between both variables.